48x+70=43x+90

Simple and best practice solution for 48x+70=43x+90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 48x+70=43x+90 equation:



48x+70=43x+90
We move all terms to the left:
48x+70-(43x+90)=0
We get rid of parentheses
48x-43x-90+70=0
We add all the numbers together, and all the variables
5x-20=0
We move all terms containing x to the left, all other terms to the right
5x=20
x=20/5
x=4

See similar equations:

| 5.8n+2.7=28.8 | | -17-8x=35-6x | | -5/6=-5/7z | | 12x+27+15x-15=60 | | s*6+24=114 | | -19=10w | | -0.06m=702 | | 52m+11=2 | | 7+x=8+2x | | 7/3=-8u | | 7b+9=3+4b | | 7p-5=8p-2p | | 9x=7x=22 | | 3x+9=2x+18 | | u/8=-53 | | 8x+7/3x+2=4x+5/2x+3 | | 1122=n(n+1) | | 3(x-2)-(5-x)=5 | | -2(1+3a)=56 | | 3+0.5(4x+8)=9-2x | | (x+3)/3=(2x-1)/7 | | 17(3x-5)-(9x-1)=B(3x-6) | | 400≠20x+240=240 | | 2(x+3)=5x+29 | | 2(x-3)^2-4=14 | | 2x^2+1x+7=0 | | 10x–2=3x+23 | | 4x+1=2(2+3) | | 5x=90+200+10 | | x/4=3/28 | | 5(2x+5)+3=8x+38 | | 6+12=4x-8 |

Equations solver categories